SISTEM PENDUKUNG KEPUTUSAN MANAJEMEN KOMPLAIN MENGGUNAKAN METODE SIMPLE MULTI-ATTRIBUTE RATING TECHNIQUE EXPLOITING RANK - Wiji Setiyaningsih (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
During this time the complaint management at PT. X is still less than optimal, this is due to the technical area and the development of Internet network services Pay TV PT. X very broad, covering all areas of the city of Surabaya and Sidoarjo. In addition, the submission of a complaint by the customer served through telephone communication with customer service section (CS). Weaknesses in the delivery of this complaint, sometimes difficult connected telephone communication on the part of CS for busy communications, where if in some time not connected communication with CS branch in Surabaya, the direct telephone communication automatically connected to the PT. X central Jakarta. It is often a misconception for Surabaya branch some managerial Jakarta Centre to handle complaints about bad customer. There is also to convey customer complaints directly with the coming into office of PT. X Surabaya. Nature of complaints submitted by customers varied, and from the technical side of the settlement sometimes complains that no once can directly, this is because usually there are technical problems that require analysis and long turnaround time. In addition, weaknesses in the management of the current complaint are the inability to handle the complaint in accordance urgency priority level. By building a Decision Support System Using Web Based Complaint Management SMARTER method, so as to accommodate the customer complaints effectively, and to provide decision support priorities in settling the complaint in accordance with the level of difficulty and areas of disturbance disorders, as well as the creation of a report that is capable of handling complaints clicking history of early receipt of customer complaint to completion. This is one of them functioned to support the development of the policy-making process-development of product technology features PT. X Surabaya.